Universal Jurisdiction - Chinchón Álvarez, Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This article provides a brief approach to the principle of Universal Jurisdiction, examining its concept, configuration and theoretical basis, as well as some of the issues that has raised its modern application. Especially those that explain in whole or in part the current state of affairs from the process that started in the beginning of this century.